2016
DOI: 10.1186/s12885-016-2747-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in six major subtypes of melanoma: descriptive epidemiology

Abstract: BackgroundMelanoma accounts for the majority of skin cancer deaths. It has over thirty different subtypes. Different races have been observed to differ in multiple aspects of melanoma.MethodsSEER (Surveillance, Epidemiology, and End Results) data on six major subtypes, namely melanoma in situ (MIS), superficial spreading melanoma (SSM), nodular melanoma (NM), lentigo maligna melanoma (LMM), acral lentiginous melanoma malignant (ALM), and malignant melanoma NOS (NOS), were analyzed. The racial groups studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 32 publications
1
87
0
2
Order By: Relevance
“…Our study revealed the unique characteristic of Japanese melanoma patients. Notably, the most common clinical type was ALM (40.4%); in contrast, the proportion of ALM among non‐Hispanic whites in the SEER database was only 1.5% . Therefore, 44.7% of all melanoma developed in the hand or foot.…”
Section: Discussionmentioning
confidence: 98%
“…Our study revealed the unique characteristic of Japanese melanoma patients. Notably, the most common clinical type was ALM (40.4%); in contrast, the proportion of ALM among non‐Hispanic whites in the SEER database was only 1.5% . Therefore, 44.7% of all melanoma developed in the hand or foot.…”
Section: Discussionmentioning
confidence: 98%
“…Recent clinical trials have revealed that immune checkpoint inhibitors significantly improved the OS of patients with advanced melanoma . However, these previous studies comprised mainly white populations, in which SSM and LMM are the major clinical types of melanoma . In contrast, Asians manifest a distinct clinicopathological type of melanoma from that of whites and show much higher frequencies of ALM and MUC, which have been shown to be less susceptible to immune checkpoint inhibitors .…”
Section: Discussionmentioning
confidence: 99%
“…Although this might reduce their requirements for sun protection, there are no studies or guidelines to our knowledge that establish a less stringent but “safe” standard for people with darker skin. The melanoma subtypes associated with sun exposure, such as superficial spreading melanoma, are rare in darker‐skinned populations . The more frequent melanoma subtypes in the darker‐skinned population, such as acral lentiginous melanoma, tend to occur on non‐sun‐exposed areas of the body and are less related to sun exposure .…”
Section: Discussionmentioning
confidence: 99%